THE FUNCTIONS OF DERIVATIONAL SUFFIXES IN INSPIRATIONAL BOOK WRITTEN BY MARIA AND ELIZABETH RAHAJENG “BECOMING UNSTOPPABLE” - Putri, I Dewa Ayu Agung Bintang Maharani (Universitas Lambung Mangkurat, 2023)
This study focuses on the derivational suffixes found in Maria and Elizabeth Rahajeng's book